Relative bioavailability and pharmacokinetic comparison of calcium glucoheptonate with calcium carbonate - MSS Wiria; Hung Manh Tran; Phuc H. B. Nguyen; Olivia Valencia; Surajit Dutta; Etienne Pouteau (Wiley, 2020)
Abstract Adequate calcium intake is important for the prevention of bone loss and osteoporosis. For some populations such as those of Southeast Asia where calcium intake is very low, supplements represent a suitable dietary source of calcium. The objective of this study was to compare the relative oral bioavailability of calcium from calcium glucoheptonate, a highly soluble calcium salt containing 8.2% of elemental calcium, to that of calcium carbonate. A single‐dose, randomized‐sequence, open‐label, two‐period crossover study, with a 7‐day washout period, was conducted in 24 Indonesian healthy adult volunteers. After a 12‐hour (overnight) fast, subjects received either two oral ampoules of 250 mg/10 mL of calcium glucoheptonate each or one effervescent tablet of calcium carbonate containing 500 mg of elemental calcium. The relative oral bioavailability of calcium from calcium glucoheptonate as compared to calcium carbonate was 92% within 6 hours and 89% within 12 hours after study drug administration. The 90% confidence intervals for the mean test/reference ratios of the maximum plasma concentration and the area under the concentration‐time curve at 12 hours post‐administration were 77.09%-120.31% and 60.58%-122.30%, respectively. Five subjects experienced a total of eight adverse events which were all mild and transient; no serious adverse events or deaths were reported. These results indicate that calcium glucoheptonate is associated with a high relative bioavailability of calcium compared to calcium carbonate, and is well‐tolerated. Calcium glucoheptonate might thus be a potential choice for calcium supplementation in Southeast Asian populations.